A meta-analysis of the ecological impacts of viticultural practices on soil biodiversity - Laure Gontier; Battle Karimi; Jean-Yves Cahurel; Lionel Ranjard (IVES Technical Reviews)
Soil quality and adequate soil management are key levers for sustainable viticulture. Until now, a global and comprehensive analysis of the impact of viticultural practices on soil biodiversity was lacking. We conducted a meta-analysis of the international literature to rank viticultural production systems and practices according to their impact. Tillage, bare soil and mineral fertilisation are significantly deleterious to the whole soil biodiversity, whereas cover crops, organic fertilisers and pruning wood inputs are beneficial.